การประเมินความเสี่ยงของดินถล่มโดยใช้ตัวแปรความชื้นของดิน - พงษ์ศักดิ์ มาลัย (จุฬาลงกรณ์มหาวิทยาลัย, 2007)
This research aims to propose an empirical criteria to warn landslide susceptibility based on the water carrying capacity of top soil. The used soil had been collected from Namkor, Lumsak, Phetchabun where large scale landslide occurred a few years ago. A series of laboratory tests had been conducted to obtain its water losing potential under various circumstances. The water recession constant (k) obtained from laboratory tests was then applied in calculation of the Antecedent Precipitation Index (API) of the area. The parameters being studied in the laboratory tests were temperature and water recharging period. It was found that temperature moderately affected the value of water recession constant. Namely high temperature caused large amount of losing water and higher value of k. As a consequence, the water recession constant adopted in compulsion of API varies according to the season; i-e k=0.7 in summer and 0.9 in rainy and winter. An empirical criteria based on the increment of accumulate API was proposed. It was found that the stiffest ingredient of accumulated API occurs mostly during 240-270 days. The slope of the accumulated API formed a liner correlation to the yearly peak API (which usually occurs at 250 days or later). The refer slope of the accumulated API at 240-270 days can be a good indicator for prediction peak API of the year.